Viking Age garden plants from southern Scandinavia: diversity, taphonomy and cultural aspects - Sloth, Pernille Rohde; Hansen, Ulla Lund; Karg, Sabine (Danish Journal of Archaeology, 2012)
Plant finds recovered from archaeological sites in southern Scandinavia dated to the Viking Age reflect the diversity of useful plants that were cultivated and collected. This review presents the results of 14 investigations of deposits that are dated between AD 775 and 1050. The site types are categorized as agrarian, urban, military and burials. Garden plants are unevenly distributed, as the greatest diversity is recorded in features from urban contexts. We argue that taphonomic processes played an important role in the picture displayed. Archaeobotanical research results from neighbouring regions suggest that Viking Age horticulture has its roots in older traditions, and that the spectrum of garden plants is influenced by central and north-western European horticultural customs, which were to a great extent shaped by Roman occupation.